Body dysmorphic disorder in patients with acne: treatment challenges - Kobusiewicz, Aleksandra; Tomas-Aragones, Lucia; Marron, Servando; Zalewska-Janowska, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Body dysmorphic disorder (BDD) is defined as a constant preoccupation with one or more non-existent or slight defects or flaws in the physical appearance, often resulting in repetitive behaviours like mirror checking and camouflaging. The prevalence is around 2% in the general population with up to 10% in dermatology patients [1, 2]. The prevalence of BDD in patients with acne ranges between 9% and 15% [3]. BDD is associated with considerable psychosocial deterioration, poor quality of life, and development of comorbid mental health disorders, including obsessive compulsive disorder, depression, social anxiety and alcohol or illicit drug use [4]. Such patients suffer tremendously and are at high risk of suicide. The rate of suicidal ideation reaches 79.5%. Of this number, nearly 27.6% make failed suicidal attempts each year and 0.3% of these attempts are successful [5]. We present a case of body dysmorphic disorder in a patient with acne as they are usually underdiagnosed and left without adequate treatment and referral. We stress the importance of screening for this condition by dermatologists and engaging a mental health professional so as to manage these challenging patients in the view of high prevalence, functional impairment and risk of suicide.